2023
DOI: 10.3389/fmolb.2023.1209974
|View full text |Cite
|
Sign up to set email alerts
|

Antibody production and tolerance to the α-gal epitope as models for understanding and preventing the immune response to incompatible ABO carbohydrate antigens and for α-gal therapies

Abstract: This review describes the significance of the α-gal epitope (Galα-3Galβ1-4GlcNAc-R) as the core of human blood-group A and B antigens (A and B antigens), determines in mouse models the principles underlying the immune response to these antigens, and suggests future strategies for the induction of immune tolerance to incompatible A and B antigens in human allografts. Carbohydrate antigens, such as ABO antigens and the α-gal epitope, differ from protein antigens in that they do not interact with T cells, but B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…35 Of note, tandem mass spectrometry (MS/MS) and antibody staining showed that mouse LRP1 N-glycans exhibit the terminal Galα1-3Galβ1-4GlcNAc (α-Gal) epitope (Figures 4B and S6), a unique carbohydrate antigen abundantly expressed on glycoconjugates of most mammals yet absent in humans. 36, 37 To determine which of these N-glycan structures are ligand(s) for hDCIR and mDCIR1, we performed an enzyme-linked lectin assay using neo-glycoproteins generated by covalent coupling of biantennary complex-type N-glycans with either terminal GlcNAc, Gal, α-Gal or α2,6-linked sialic residues to bovine serum albumin (BSA). We found that both hDCIR-ECD and mDCIR1-ECD strongly interact with biantennary complex-type N-glycans with terminal galactose residues, including those carrying the α-Gal epitope, but poorly or not at all with agalactosylated or sialylated N-glycans (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Of note, tandem mass spectrometry (MS/MS) and antibody staining showed that mouse LRP1 N-glycans exhibit the terminal Galα1-3Galβ1-4GlcNAc (α-Gal) epitope (Figures 4B and S6), a unique carbohydrate antigen abundantly expressed on glycoconjugates of most mammals yet absent in humans. 36, 37 To determine which of these N-glycan structures are ligand(s) for hDCIR and mDCIR1, we performed an enzyme-linked lectin assay using neo-glycoproteins generated by covalent coupling of biantennary complex-type N-glycans with either terminal GlcNAc, Gal, α-Gal or α2,6-linked sialic residues to bovine serum albumin (BSA). We found that both hDCIR-ECD and mDCIR1-ECD strongly interact with biantennary complex-type N-glycans with terminal galactose residues, including those carrying the α-Gal epitope, but poorly or not at all with agalactosylated or sialylated N-glycans (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…alphagal syndrome, and hypersensitivity reactions to cetuximab, a chimeric mouse-human monoclonal antibody used to treat cancers of the bowel and neck. 36,37,[65][66][67] To our knowledge, hDCIR is the first human lectin described as interacting with the a-Gal epitope carried on glycoproteins, suggesting that this lectin may play an important role in a-Gal-mediated diseases. In agreement with this idea, a recent study established that DCIR on the surface of mast cells mediates the recognition and uptake of cockroach allergen, which contains the a-Gal epitope on N-glycans, and enhances cockroach/IgE-induced mast cell activation and atopic dermatitis-like inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Neu5Gc-containing glycans are thought to be immunogenic in humans, triggering the development of a polyclonal anti-Neu5Gc humoral immune response that accommodates Neu5Gc in the context of an array of underlying glycan structures (Breimer and Holgersson, 2019). This presentation of Neu5Gc on a diverse range of underlying scaffolds differs from other carbohydrate xenoantibodies, such as anti-αGal antibodies, which are directed against a single Galα1-3Galβ1-4GlcNAc-R epitope and are triggered by early-life exposure to these glycans on commensal bacteria (Padler-Karavani and Varki, 2011;Galili, 2023). This relative simplicity may explain why αGal antibodies are reliably reported across the entire human population, whereas the extent of the anti-Neu5Gc antibody response remains controversial (Galili, 2023).…”
Section: Neu5gc As a Xenoautoantigenmentioning
confidence: 99%